Modifiye Ketonik Reçinelerin Poliüretan Üretiminde Kullanımı - Yivlik, Lütfullah Yusuf (Fen Bilimleri Enstitüsü, 2016)
Bu çalışmada siklohekzanon – formaldehit ve asetofenon – formaldehit reçineleri asit ve bazik ortamlarda üretilmiş, ve yine asit ve bazik ortamlarda azot ve fosforlu moleküller ile modifiye edimiştir. Siklohekzanon-formaldehit reçinesi ketonik ve termoplastik bir reçinedir. Kondenzasyon reaksiyonu sonucu oluşur ve siklik yapıdadır. Polar çözücülerde asetofenon – formaldehit reçinesine göre daha iyi çözünür. Kaplama, boya, yapıştırıcı gibi endüstriyel ürünlerin üretiminde kullanılır. Asetofenon – formaldehit reçinesi ve siklohekzanon – formaldehit reçinesi üretimi için farklı parametreler kullanılmıştır. Solvent sistemi, katalizör, aktivatör, keton/formaldehit oranı değiştirilerek denenen parametreler arasındadır. Bu denemeler sonucunda reçinenin en verimli ve en katı olarak ele geçtiği sistem kullanılmıştır. Asitli ortamda ketonik reçine üretimi ile ilgili literatür çok azdır. Literatürde daha öncek yapılan çalışmalarda asit ortamda yanlızca siklohekzanon – formaldehit reçinesi üretilmiştir. Bu çalışmada ise asetofenon – formaldehit reçinesinin de üretimi asitli ortamda gerçekleştirilmiştir. Asitli ortamın tercih edilme sebeplerinden biri bazik ortamda gerçekleşmeyen in situ modifikasyonlardır. Siyanürik asit ve sodyum alendronat trihidrattan elde edilen s-triazon bileşiği bazik ortamda reçine ile modifiye edilememiştir. Siyanürik asitin ortamın pH’ına göre keto veya enol durumlarında bulunması bunun en önemli sebebidir. Siyanürik asit bazik ortamda enol halindeyken, asit ortamda keto halinde bulunmaktadır. Bu nedenle asitli ortamda reçine yapımı çalışılmış ve siyanürik asit ile sodyum alendronat trihidrattan elde edilen s-triazonun modifikasyonu gerçekleştirilmiştir. Üretilen reçineler sırasıyla, asitli ortamda üretilen Siklohekzanon – Formaldehit reçinesi ve Asetofenon – Formaldehit Reçinesi, in situ izosiyanürik asit modifiye Siklohekzanon – Formaldehit Reçinesi, in situ s-triazon(etanol aminden) modifiye Siklohekzanon – Formaldehit Reçinesi, in situ s-triazon(diglikolamin) modifiye Siklohekzanon – Formaldehit Reçinesi, in situ s-triazon(alendronik asit) modifiye Siklohekzanon – Formaldehit Reçinesi, Alendronik asit modifiye Siklohekzanon – Formaldehit Reçinesi ve Alendronik asit mofiye Asetofenon – Formaldehit Reçinesidir. s-Triazon bileşikleri üre, formaldehit ve amin bileşiğinin reaksiyonu sonucu elde edilmektedir. s-Triazonun 1 molünde 2 aktif hidrojen bulunmaktadır ve formaldehitle reaksiyona girerek rahatça dimetilol oluşturabilir. Metilol türevi s-triazonlar reçine ile bazik ve asit ortamlarda kondenzasyon ürünü verebilirler. s-Triazon kullanımında kullanılan amin bileşikleri etanolamin, glikolamin ve alendronik asittir. Modifikasyonda kullanılan oran ise s-triazon/reçine oranı 2/5 veya 1/10’dur. Ayrıca reçineler primer ve sekonder aminlerle de modifiye edilmiştir. Elde edilen reçineler farklı çözünürlükler göstermişlerdir. Modifiye reçinelerin Termal Gravimetrik Analizi, FT Infrared, Nükleer Manyetik Rezonans analizleri ve çözünürlükler yapılarak oluşan ürünlerin yapı analizleri gerçekleştirilmiş ve özellikleri tespit edilmiştir. Elde edilen reçineler poliüretan köpüklerin yapımında katkı maddesi olarak kullanılmıştır. Modifiye reçineler poliüretan köpük üretiminde poliolün %25’i oranında ortama katılmış, elde edilen poliüretan köpüğün özellikleri incelenmiştir. Bu amaçla Termal Gravimetrik Analizi ve UL94 testine uygun testler kullanılmıştır. Reçinelerin modifiye edilmesinde kullanılan moleküllerdeki azot ve fosfor reçineye ve dolayısıyla poliüretana belli oranda yanmazlık sağlamaktadır. Bu sebeple reçinedeki fosfor ve azot içeriğinin kütlece yüzdesi önem kazanmaktadır. Sodyum alendronate trihidrat gibi bol fosfor içeren aminler bu sebeple tercih edilmiştir. Çalışmaya göre elde edilen sonuçlar şunlardır, siklohekzanon – formaldehit reçinesi asitli ve bazik ortamda verimli olarak elde edilebiliyor. Asetofenon – formaldehit reçinesi bazik ortamda potasyum hidroksit varlığında verimli olarak elde edilebiliyor. Reçineler s-triazon veya doğrudan amin bileşikleri ile modifiye edilebiliyor. Reçinelerin modifikasyonunda kullanılan maddeler üre, formaldehit, siyanürik asit gibi kolay bulunabilen ve ucuz malzemelerdir. Bileşiğin türüne göre reçinenin modifikasyonu sonucu çözünürlük, yanmazlık gibi bazı fiziksel özellikleri değiştirilebiliyor. Bu sayede reçinenin kullanım alannı genişletilebilir. Modifiye reçineler poliüretanın yanmazlığı gibi köpük üzerinde olumlu etkiler yaptığı ortaya çıkarılmıştır.

In this study cyclohexanone – formaldehyde and acetophenone – formaldehyde resins produced in acidic and basic media and modified by nitrogen and phosphorus containing molecules. Then new modified resins mixed with polyol to produce polyurethane foam. Different parameters used to produce acetophenone – formaldehyde and cyclohexanone - formaldehyde resins. Reaction’s catalysis changed, solvent and activator added to gain resin with high yield and better physical properties and low residual formaldehyde. In literature ketonic resins are produced mostly in basic media. There are only few studies about cyclohexanone – formaldehyde resin production in acidic conditions. The color of cyclohexanone– formaldehyde resin reported earlier was white however, resin produced in this work was red-brown. Different parameters were applied to produce cyclohexanone– formaldehyde resin with better physical properties and light color in acid media. Solvent system, activator system, catalysis system changed but the color of cyclohexanone– formaldehyde resin product was about the same red-brown color. However some physical property was different. While the cyclohexanone – formaldehyde resin produced in acidic media is soluble in ethanol, cyclohexanone – formaldehyde resin produced with base catalysis is insoluble. On the contrary, the cyclohexanone – formaldehyde resin produced in acidic media is slightly soluble in methanol while cyclohexanone – formaldehyde resin produced with base catalysis in insoluble. The cyclohexanone – formaldehyde resin produced in both acidic media and basic media showed identical FTIR spectrum and nearly identical 1H-NMR peaks. Cyclohexanone - formaldehyde resins can be produced in acid and basic media successfully. However, acetophenone – formaldehyde resin can only be produced in basic media in presence of potassium hydroxide. Acetophenone – formaldehyde resin formed in acidic media with very low yield and its softening point was about 20-250C. The main reason for synthesizing ketonic resin in acidic condition was some in situ modifications failed under basic resin formation media. Especially, in situ modification of the cyclohexanone – formaldehyde resin with cyanuric acid and s-triazone of sodium alendronate using basic catalyst were not successful. In acidic media, cyclohexanone-formaldehyde resin was successfully in situ modified with cyanuric acid and s-triazone of sodium alendronate. Different ratio of cyanuric acid/cyclohexanone were used to produce cyanuric acid modified cyclohexanone-formaldehyde resin with different physical properties such as solubility and melting temperature. Also cyanuric acid trimethylol produced by reaction between 1 mole of cyanuric acid and 3 mole of formaldehyde was used to modify cyclohexanone-formaldehyde resin. Structural determinations of the modified resins were carried out using NMR and FTIR and thermal properties were determined with TGA. Furthermore, cyclohexanone-formaldehyde resin were modified with s-triazone compounds. S-triazone were first produced by the reaction of urea, formaldehyde and amine compounds in one step. S-Triazones have 2 active free hydrogens and react with formaldehyde easily to produce dimethylol derivatives. Formed dimethylol derivatives can condense with methylols of ketonic resin in basic media and especially in acidic conditions. The amines used to produce s-triazones were ethanolamine, glycolamine and sodium alendronic acid. The ratio of s-triazone/cyclohexanone 2/5 and 1/10 were used to produce modified resins. The modified resins showed rather different solubility in organic solvents. S-triazone compounds were also produced with two step method. Dimethylol urea was first synthesized and subsequently reacted with amine compound. Similar yield of S-triazone compound were obtained. Ketonic resins such as cyclohexanone – formaldehyde and acetophenone – formaldehyde were also modified by using primary and secondary functional amines. Ethanolamine, glycolamine and alendronic acid were directly added to the flask during ketonic resin preparation. This is a typical in situ modification of ketonic resin. The modified resins showed different solubility in solvents. The modified resins were examined first with TLC and then FTIR, 13C NMR, 1H NMR and 31P NMR spectroscopy. FTIR spectroscopy was used to elucidate the structure of modified resins. Carbonyl peak of ketonic resin and S-triazone compounds appeared at 1700 cm-1 and 1650-1600 cm-1 respectively. 13C-NMR spectroscopy also gives some information. While carbonyl carbon peaks of ketonic resin appeared at about 210-220 ppm with low intensity, carbonyl carbons of s-triazone structure were observed at about 150-160 ppm. Cyclohexanone – formaldehyde resins modified with alendronic acid and S-triazone of sodium alendronate showed peaks at about 15-20 ppm in 31P-NMR spectrum. By the adding these resins to improve industrial polymer’s fire resistance future gives to inspires to other studies. The produced resins are, CF- Resin, AF-Resin, in situ isocyanuric acid modified CF-Resin, in situ s-triazone (ethanol amine) modified CF-Resin, in situ s-triazone(diglikolamine) modified CF-Resin, in situ s-triazone(alendronic asit) modified CF-Resin. Alendronic acid modified CF-Resin and Alendronic acid modified AF-Resin. The compounds used in the modification of resins, which are readily available and are inexpensive materials such as urea, formaldehyde, cyanuric acid, ethanol amine and glycol amine. According to the type of the compound used in the modification of resin changed physical properties such as solubility and flammability. Thus, the use of resin allows for expansion in the field application has emerged. Modified compounds has a positive effects on the inflammability of rigid polyurethane foams. Cyclohexanone – formaldehyde resins modified with these s-triazone of ethanolamine, glycolamine, alendronic acid were used in the production of rigid polyurethane foam which is widely used in industry. Modified ketonic resins were added in to polyol component with 25wt% of polyol and mixed with hardener component to produce rigid polyurethane foam. Polyol component contained catalyst, blowing agent and small amount of water. After two days of production, the rigid foam samples were tested with UL94, TGA and combustion tests. Amine and s-triazone modified cyclohexanone – formaldehyde resins contains nitrogen. Furthermore, cyclohexanone – formaldehyde resin modified with alendronic acid and s-triazone of alendronic acid contain both nitrogen and phosphorus atoms. These nitrogen and phosphorous atoms give fire retardant feature to polyurethane foam containing these modified resins. Percentage of phosphorus atoms in final polyurethane foam were in the range of 1–2 wt%. Polyurethane foam containing amine and s-triazone modified ketonic resin showed some fire retardant property. As expected, polyurethane containing ketonic resin modified with alendronic acid and s-triazone of alendronic acid showed much better fire retardant property. Rigid polyurehane foam containing about xx% ketonic resin or modified ketonic resin were tested with TGA. The residue at 650 0C were as follows: PU containing cyclohexanone– formaldehyde resin (PUF):7%, PU containing 2:5 ethanolamine s-triazone modified cyclohexanone– formaldehyde resin(PUYM11):13%, PU containing 1:4 cyanuric acid modified cyclohexanone– formaldehyde resin(PUYM16):15%, PU containing 2:5 glycol amine s-triazone modified cyclohexanone– formaldehyde resin(PUYM14):18 % and PU containing 2:5 alendronic acid modified acetophenone– formaldehyde resin(PUYM2):20%. Furthermore burning test was carried out by horizontal burning of the bar with about 2mmx4mmx100 mm prepared from polyurethane foam. Burning stops before 10 seconds. Elapsed time is as follows: YM2: 3 seconds, YM11: 5 seconds, PUYM 14: 11 seconds, PUYM 16:12 seconds.
Use Of Modified Ketonic Resins In Polyurethane Foam
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2016
Keywords: Reçine; Poliüretan; Köpük; Asetofenon; Formaldehit; Siklohekzanon; Asit Ortamda Reçine; Asit Ortamda Aldol; Ketonik Reçine; Sert Köpük; Siyanürik Asit Modifikasyonu; Yanmazlık; Yanmaz Poliüretan; Resin; Polyurethane; Foam; Acetophenone; Formaldehyde; Cyclohexanone; Resin In Acid Media; Aldol In Acid Media; Ketonic Resin; Rigid Foam; Cyanuric Acid Modification; Flame Retardancy; Flame Retardant Polyurethane